Anti-protein arginine methyltransferase 5 (PRMT5) antibodies is associated with interstitial lung disease in rheumatoid arthritis - Renliang Huang; Jiaxi Guo; Qiaomiao Zhou; Heqing Huang; Shaowei Lin; Yikai Lin; Frank Petersen; Xinhua Yu; Aiping Ma (Scientific Reports)
Abstract Recently, anti-protein arginine methyltransferase 5 (PRMT5) antibodies has been identified a novel marker for systemic sclerosis (SSc). The present study aimed to to explore the association between anti-PRMT5 antibodies and rheumatoid arthritis (RA). The study recruited a cohort of 33 patients diagnosed with SSc, 87 patients with RA, and 31 healthy control subjects. Serum levels of the anti-PRMT5 antibodies were measured using a double-antigen sandwich enzyme-linked immunosorbent assay (ELISA). Patients with SSc exhibited higher serum levels (p < 0.001) and seropositivity rates (48.5% vs. 0%, p < 0.0001) of anti-PRMT5 antibodies compared to healthy subjects. Notably, serum levels of anti-PRMT5 antibodies were significantly elevated in patients with RA compared to healthy controls (p < 0.001), with a corresponding increase in the rate of seropositivity (14.9% vs. 0%, p < 0.05). Receiver operating curve analysis for anti-PRMT5 antibody levels yielded area under the curve values of 0.768 for distinguishing RA patients from healthy controls, and 0.903 for distinguishing SSc patients from controls. Furthermore, elevated levels of anti-PRMT5 antibodies were significantly associated with the presence of interstitial lung disease (ILD) (p < 0.0001) and antinuclear antibody positivity (p < 0.01). This study not only confirms the association of the anti-PRMT5 antibodies with SSc but also, for the first time, demonstrates a significant association between the anti-PRMT5 antibodies and RA, particularly in the context of RA-associated ILD.